Law and legal education in the information age: quo vadis? - Zulhuda, Sonny (International Islamic University Malaysia, 2011)
Law as a social instrument must be readily capable to embrace the new challenges brought about by the use of technology in the society it serves. In the Information Age where information is viewed as an asset, the law should adopt new approaches so as to keep itself relevant and effective. This paper demonstrates the nature of the Information Age and how law should respond. It also includes steps for law educational institutions to take in reforming legal education and curriculum to facilitate a better legal scholarship in the Information Age.